Injury incidence and characteristics in South African school first team rugby: A case study - Tee, J; Lebatie, F; Till, K; Jones, B (South African Journal of Sports Medicine, 2017)
Background: Despite its apparent popularity, participation in the sport of rugby union is accompanied by a significant risk of injury. Concerned parties have recently questioned whether this risk is acceptable within school populations. This is difficult to assess within the South African schools’ population as no recent longitudinal injury studies exist. Objectives: To determine the training habits, rugby-related exposure and injury risk within a population of South African high school first team rugby players. Methods: Training and match exposure in both school and provincial competition were examined and the resultant injuries were longitudinally observed for the duration of a South African high school rugby season. Results: Match (79, 95%CI 52-105 injuries/1 000 h) and training (7, 95%CI 3-11 injuries /1000h) injury incidences were demonstrated to be greater than previously reported incidences in similar populations in England and Ireland. Weeks where players were exposed to both school and provincial competition (34, 95%CI 19-49 injuries /1 000 h) had significantly (p<0.05) greater injury incidences than during school competition alone (19, 95%CI 12-26 injuries /1 000 h). Conclusion: The injury risk demonstrated was greater than expected and represents reasons for concern. Possible reasons for the high injury incidence recorded may be the frequency of games played within the season, and the overlap of school and provincial competitions. It should be noted that these results were taken from one school over one season and might not be representative of the incidence of school rugby injuries overall. However, this research demonstrates the need for a multischool longitudinal study within South African schools rugby to determine the overall risk.